Technical Aspects of Laparoscopic Distal Pancreatectomy for Benign and Malignant Disease: Review of the Literature - T. de Rooij; R. Sitarz; O. R. Busch; M. G. Besselink; M. Abu Hilal (Gastroenterology Research and Practice)
Distal pancreatectomy is the standard curative treatment for symptomatic benign, premalignant, and malignant disease of the pancreatic body and tail. The most obvious benefits of a laparoscopic approach to distal pancreatectomy include earlier recovery and shorter hospital stay. Spleen-preserving distal pancreatectomy should be attempted in case of benign disease. Spleen preservation can be achieved preferably by preserving the splenic vessels (Kimura technique), but also by resecting the splenic vessels and maintaining vascularity through the short gastric vessels and left gastroepiploic artery (Warshaw technique). Several studies have suggested a higher rate of spleen preservation with laparoscopy. The radical antegrade modular pancreatosplenectomy has become mainstay for treating pancreatic cancer and can be performed laparoscopically as well. Evidence on the feasibility and safety of laparoscopic distal pancreatectomy for cancer is scarce. Despite the obvious advantages of laparoscopic surgery, postoperative morbidity remains relatively high, mainly because of the high incidence of pancreatic fistula. For decades, surgeons have tried to prevent these fistulas but to date no strategy has been confirmed to be effective in 2 consecutive randomized studies. Pragmatic multicenter studies focusing on technical aspects of laparoscopic distal pancreatectomy are lacking and should be encouraged.